2000
DOI: 10.1097/00003246-200008000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in tissue oxygen consumption and extraction after trauma and hemorrhagic shock

Abstract: Because the liver experienced the most severe reduction in VO2 associated with an unchanged oxygen extraction capacity, this organ appears to be more vulnerable to hypoxic insult after hemorrhagic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
2
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 26 publications
4
54
2
2
Order By: Relevance
“…Although hyperkalemia and hyponatremia developed in the DHS and SHS groups, electrolytes normalized with resuscitation. As previously described, this model of hemorrhagic shock was associated with a significant decrease in hemoglobin in the DHS and SHS groups that further declined in the R group (18). …”
Section: Resultssupporting
confidence: 64%
“…Although hyperkalemia and hyponatremia developed in the DHS and SHS groups, electrolytes normalized with resuscitation. As previously described, this model of hemorrhagic shock was associated with a significant decrease in hemoglobin in the DHS and SHS groups that further declined in the R group (18). …”
Section: Resultssupporting
confidence: 64%
“…It has been shown that cardiac output, left ventricular performance and organ blood flow in the liver, small intestine and kidney decreased significantly following T-H and resuscitation (6,7). A prolonged depression of cardiovascular function following T-H, despite fluid resuscitation was also reported by other investigators (8)(9)(10).…”
Section: Introductionmentioning
confidence: 61%
“…This procedure was performed as described earlier (6). For surgery, the rats were fasted for 16 h prior to the procedure but allowed water ad libitum, anesthetized with isoflurane (Minrad, Bethlehem, PA, USA) and restrained in a supine position.…”
Section: Trauma-hemorrhage Proceduresmentioning
confidence: 99%
“…Rats were subjected to hemorrhage or sham operation as described earlier (5). The rats fasted overnight (water allowed ad lib) and then were anesthetized with isoflurane (Minrad, Bethlehem, PA, USA) and restrained in a supine position, before surgery.…”
Section: Hemorrhage Proceduresmentioning
confidence: 99%
“…Hemorrhagic shock also causes decreased cardiac output, stroke volume and cardiac contractility (±dP/dt) (1)(2)(3). Hypoxia and reperfusion injury result in dysregulation of critical molecular pathways and bioprocesses (4)(5)(6)(7)(8)(9). The predominant causes for mortality following hemorrhagic shock are sepsis and multiple organ failure (10).…”
Section: Introductionmentioning
confidence: 99%